Anda di halaman 1dari 8

ECEN 314: Signals and Systems

Solutions to HW 3 Problem 1.27 (a) y(t) = x(t 2) + x(2 t) Let us check for linearity. x1 (t) y1 (t) = x1 (t 2) + x1 (2 t) x2 (t) y2 (t) = x2 (t 2) + x2 (2 t) ax1 (t) + bx2 (t) = x3 (t) y3 (t) = x3 (t 2) + x3 (2 t) = ax1 (t 2) + bx2 (t 2) + ax1 (2 t) + bx2 (2 t) = a(x1 (t 2) + x1 (2 t)) + b(x2 (t 2) + x2 (2 t)) = ay1 (t) + by2 (t) Hence linear. Let us check for time-invariance. x1 (t) y1 (t) = x1 (t 2) + x1 (2 t) x1 (t to ) = x2 (t) y2 (t) = x2 (t 2) + x2 (2 t) = x1 (t to 2) + x2 (2 t to ) = y1 (t to ) Note that y1 (t to ) = x1 (t to 2) + x1 (2 t + to ). Hence time-variant. Suppose |x(t)| < B. Then y(t) < B + B = 2B (because |x(t 2)| < B and |x(2 t)| < B). Hence stable. Not memoryless as the present output at time t depends on t 2. Non-Causal because y(-1)=x(-3)+x(3). So depends on future inputs.

(b) y(t) = [cos(3t)]x(t)

Let us check for linearity. x1 (t) y1 (t) = [cos(3t)]x1 (t) x2 (t) y2 (t) = [cos(3t)]x2 (t) ax1 (t) + bx2 (t) = x3 (t) y3 (t) = [cos(3t)]x3 (t) = [cos(3t)] ax1 (t) + bx2 (t) = ay1 (t) + by2 (t) Hence linear. Let us check for time-invariance. x1 (t) y1 (t) = [cos(3t)]x1 (t) x1 (t to ) = x2 (t) y2 (t) = [cos(3t)]x2 (t) = [cos(3t)]x1 (t to ) = y1 (t to ) Note that y1 (t to ) = [cos(3(t to ))]x1 (t to ). Hence time-variant. Stable as |y(t)| < , when |x(t)| < B. Memoryless as the output at time t depends only on inputs at time t. Clearly causal.
2t

(c) y(t) =

x( )d

Let us check for linearity.


2t

x1 (t) y1 (t) =
2t

x1 ( )d

x2 (t) y2 (t) =
2t

x2 ( )d

ax1 (t) + bx2 (t) = x3 (t) y3 (t) =

x3 ( )d

2t

=
2t

ax1 ( ) + bx2 ( ) d
2t

= a

x1 ( )d + b

x2 ( )d

= ay1 (t) + by2 (t) Hence linear. Let us check for time-invariance.
2t

x1 (t) y1 (t) =
2t

x1 ( )d

x1 (t to ) = x2 (t) y2 (t) =
2t

x2 ( )d

x1 ( to )d
2tto

x1 ( )d

= y1 (t to )
2(tto )

Note that y1 (t to ) =

x1 ( )d . Hence time-variant.

Suppose x(t) = 1. Then y(1) = . Hence unstable.


2

Non-causal because, y(1) depends on the value of x(t) at t = 2, as y(1) =

x1 ( )d .

Clearly has memory by the above argument. 0 t<0 . x(t) + x(t 2) t 0

(d) y(t) =

By using the same method as we used for the above parts, it is linear, causal and stable and

not memoryless. Now let us check for time-invariance. x1 (t) y1 (t) = x1 (t to ) = x2 (t) y2 (t) = = 0 t<0 x1 (t) + x1 (t 2) t 0 0 t<0 x2 (t) + x2 (t 2) t 0

0 t<0 x1 (t to ) + x1 (t to 2) t 0 = y1 (t to ) This is because y1 (t to ) = Hence time-variant. 0 t < to x1 (t to ) + x2 (t to 2) t to

(e) y(t) =

0 x(t) < 0 . x(t) + x(t 2) x(t) 0

By using the same technique as was used for the previous problems, this is time-invariant, not memoryless, stable, causal. Let us check for linearity. Suppose let the input be x1 (t) = 1 for all t. Then the output y1 (t) corresponding to the input x1 (t) is y1 (t) = 2. t Let us now take the input x2 (t) = x1 (t) = 1. If the system is linear, then we should get y2 (t) = y1 (t) = 2, where y2 (t) is the output to the input x2 (t). Since x2 (t) < 0, the output y2 (t) = 0 = y1 (t). Hence not linear. (f) y(t) = x(t/3) This is linear and stable. It is not memoryless (for example, the output at time t = 3 depends on input at t = 1). It is non-causal as well. Let us see whether it is time-invariant. x1 (t) y1 (t) = x1 (t/3) x1 (t to ) = x2 (t) y2 (t) = x2 (t/3) t = x1 to 3 = y1 (t to ) This is because y1 (t to ) = x1 4 t to . 3

Hence time-variant.
dx(t) dt

(g) y(t) =

This is linear, as well as time-invariant. This is not memoryless as y(t) depends on x(t t) in calculating dx(t) , since dx(t) = limt0 x(t)x(tt) . dt dt t

Problem 1.28 (a) y[n] = x[n] Let us check for linearity. x1 [n] y1 [n] = x1 [n] x2 [n] y2 [n] = x2 [n] ax1 [n] + bx2 [n] = x3 [n] y3 [n] = x3 [n] = ax1 [n] + bx2 [n] = ay1 [n] + by2 [n] Hence linear. Let us check for time-invariance. x1 [n] y1 [n] = x1 [n] x1 [n no ] = x2 [n] y2 [n] = x2 [n] = x1 [n no ] = y1 [n no ] Note that y1 [n no ] = x1 [n + no ]. Hence time-variant. This is stable as |y[n]| < , if |x[n]| < B. Non-causal because, y[1] depends on the value of x[1]. Clearly has memory by the above argument.

(b) y[n] = x[n 2] 2x[n 8] By using the same technique as used for the above problem, it is linear, time-invariant, causal, stable. This is not memoryless. 5

(c) y[n] = nx[n] x1 [n] y1 [n] = nx1 [n] x2 [n] y2 [n] = nx2 [n] ax1 [n] + bx2 [n] = x3 [n] y3 [n] = nx3 [n] = n(ax1 [n] + bx2 [n]) = ay1 [n] + by2 [n] Hence linear. Let us check for time-invariance. x1 [n] y1 [n] = nx1 [n] x1 [n no ] = x2 [n] y2 [n] = nx2 [n] = nx1 [n no ] = y1 [n no ] Note that y1 [n no ] = (n no )x1 [n no ]. Hence time-variant. This is not stable because if x[n] = 1 for all n, then y[n] as n . Memoryless because, y[n] depends only on x[n]. It is also causal.

(d) y[n] = E{x[n 1]}, where E is the even part. E{x[n 1]} = x[n 1] + x[1 n] 2

This is linear, stable, not memoryless, non-causal. This is time-variant which can be seen by using exactly the same steps as we used for Problem 1.27 (a) with t replaced by n. (e) y[n] = x[n] n1 0 n=0 . x[n + 1] n 1

This is linear and stable, not memoryless and non-causal. Let us check for time-invariance.

x1 [n]

x1 [n no ] = x2 [n]

= = This is because y1 [n no ] = Hence time-variant.

x1 [n] n1 0 n=0 y1 [n] = x1 [n + 1] n 1 n1 x2 [n] 0 n=0 y2 [n] = x2 [n + 1] n 1 n1 x1 [n no ] 0 n=0 x1 [n + 1 no ] n 1 y1 [n no ]

x1 [n no ] n no + 1 0 n = no x1 [n + 1 no ] n no 1

x[n] n 1 0 n=0 . (f) y[n] = x[n] n 1 Following exactly the same steps, it is easy to see from Problem 1.28 (e) that it is linear and time-variant. It is causal, memoryless and stable. (g) y[n] = x[4n + 1] This system is linear as well as stable. Further it is non-causal and memoryless. Let us check for time-invariance. x1 [n] y1 [n] = x1 [4n + 1] x1 [n no ] = x2 [n] y2 [n] = x2 [4n + 1] = x1 [4n + 1 no ] = y1 [n no ] This is because y1 [n no ] = x[4(n no ) + 1] = x1 [4n 4no + 1]. Hence time-variant.

Problem 1.31 7

(a) Note that x2 (t) = x1 (t)x1 (t2). Therefore using linearity we get y2 (t) = y1 (t)y1 (t2). See the gure below. (b) We see that x3 (t) = x1 (t + 1) + x1 (t). y1 (t + 1) + y1 (t). See the gure below. Therefore using linearity we get y3 (t) =

y(t)
2 2

y(t)
3

0 2

Problem 1.36 (a) If x[n] is periodic ejo (n+N )T =e (2/To )N T = 2k


jo nT

, where o = 2/To . This implies that (T /To ) = k/N = rational number

(b) If T /To = p/q, then x[n] = ej2n(p/q) . Then the fundamental period is q/gcd(p, q) (from Problem 1.35), and therefore the fundamental frequency is 2 2 p o T gcd(p, q) = gcd(p, q) = gcd(p, q) q p q p

(c) From part (b) above, p/gcd(p, q) periods of x(t) are needed to form a single period of x[n].